2017
DOI: 10.1089/chi.2017.0082
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Plasma TRB3 and Sestrin 2 Levels in Obese and Normal-Weight Children

Abstract: Both TRB3 and sestrin 2 may contribute to the development of obesity and its complications and can be considered interesting therapeutic target for the treatment of obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 40 publications
2
20
0
Order By: Relevance
“…The sensitivity was 64% and specificity was 44%. These results go with the results of the study conducted by Nourbakhsh et al [2017] which revealed low levels of sestrin 2 in obese children when compared to children with normal weight and these levels were negatively correlated with the BMI [17]. Also, Lee et al [2012] and chai et al…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The sensitivity was 64% and specificity was 44%. These results go with the results of the study conducted by Nourbakhsh et al [2017] which revealed low levels of sestrin 2 in obese children when compared to children with normal weight and these levels were negatively correlated with the BMI [17]. Also, Lee et al [2012] and chai et al…”
Section: Discussionsupporting
confidence: 88%
“…A decrease in the intracellular levels of sestrin 2 can lead many adverse sequelae such as oxidative damage, mitochondrial dysfunction, and insulin resistance [14,15]. The investigation of sestrin 2 levels in obese and/or T2DMpatients revealed controversial results [14,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…In present study, the correlation between Sestrin2 and HDL might be associated with AMPK activation. Consistent with our view, Nourbakhsh et al [32] also revealed that there was a positive correlation between Sestrin2 and HDL.…”
Section: Discussionsupporting
confidence: 92%
“…A recent study in rats induced to have diabesity showed that TRB3 is increased in the adipose tissue and that TRB3 silencing increased insulin response in this tissue and the systemic insulin sensitivity (Sun et al, 2017). Since TRB3 protein level is reported to be increased in the blood of patients with obesity (Nourbakhsh et al, 2017), this protein involvement in adipose tissue insulin resistance is likely. However, it is still needed to run studies in adipose tissue from subjects with diabesity.…”
Section: Adipose Tissuementioning
confidence: 99%